Susceptibility of lower limb hypodermis as a reaction to systemic hydrostatic impulse: ultrasonographic evaluation - Stefańczyk, Ludomir; Marchwicka-Wasiak, Magdalena; Grzelak, Piotr (Menopause Review/Przegląd Menopauzalny, 2004)
The basis of ailments connected with chronic venous insufficiency often experienced by women is the accumulation of tissue fluid and the following humoral reactions. It is assumed that the reason for this is the high level of vascular endothelium permeability as a result of increased levels of estrogens. Based on ultrasound evaluations made in 33 women and 37 men we confirmed significant differences in the reaction of hypodermis to the systemic hydrostatic impulse. The thickness of the subcutaneous tissue of the thigh and calf changes in women to a greater extent than in men, and the correlation between this response and the impulse scale is lower, which suggests the different operation of the hypodermic buffer system in both genders. Ultrasound seems to be a useful method in monitoring the course of the disease connected with leg edema and the efficiency of treatment.